Gold-Derived Molecules as New Antimicrobial Agents - Ratia, Carlos; Soengas, Raquel G.; Soto, Sara M. (Frontiers in Microbiology, 2022)
Antimicrobial resistance is considered one of the three most important health problems by the World Health Organization. The emergence and spread of an increasing number of antimicrobial-resistant microorganisms make this a worldwide problem. Antibiotic-resistant bacteria are estimated to be the cause of 33,000 deaths in Europe and 700,000 worldwide each year. It is estimated that in 2050 bacterial infections will cause 10 million deaths across the globe. This problem is concomitant with a decrease in the investment and, therefore, the discovery and marketing of new antibiotics. Recently, there have been tremendous efforts to find new effective antimicrobial agents. Gold complexes, with their broad-spectrum antimicrobial activities and unique modes of action, are particularly relevant among several families of derivatives that have been investigated. This minireview revises the role of gold-derived molecules as antibacterial agents.